FUNCTIONS OF CLAUDIN-7 IN THE SELF-RENEWAL OF INTESTINAL EPITHELIUM - Xing, Tiaosi (East Carolina University)
Tight junctions (TJ) are located at the most apical region of the junctional complex and contain many integral membrane proteins. Claudin 7 (Cldn7) is a TJ membrane protein located at the apical TJ and basolateral side of intestinal epithelial cells. Deletion of Cldn7 by gene-targeting leads to the inflammatory bowel disease (IBD)-like phenotype in mice, which includes weight loss, diarrhea, mucosa ulceration, and severe intestinal epithelial damage. We hypothesize that Cldn7 plays a critical role in regulating intestinal crypt stem cell functions. In this study, we report for the first time that Cldn7, a TJ membrane protein, controls intestinal stem cell survival, self-renewal, and differentiation, an unexpected and novel role for a TJ proteins. Gene-deletion of Cldn7 in intestines displayed the significant alteration of expression profiles with striking downregulation of intestinal crypt stem cell markers, such as olfm4, dislocated proliferative cells, and disrupted epithelial cell differentiation. In addition, Cldn7- deficient crypts from small and large intestines were unable to survive and form organoids, highlighting the functional impairment of crypt stem cells in the absence of Cldn7. Remarkably, the Cldn7 expressing organoids with buddings underwent the rapid cell degeneration within days after turning off Cldn7 expression in the culture. We identified that activation of Wnt/[beta]-catenin signaling rescued the organoid defects caused by Cldn7 deletion in small intestine. Using a genome-wide gene expression approach and subsequent verifications by cell and molecular analyses, we have also identified notch signaling, Wnt signaling and hippo signaling as the key pathways involved in Cldn7 deletion-mediated defects in the large intestine. Disrupted cell differentiation of intestinal epithelium could be due to the suppression of notch signaling. Olfm4 was significantly decreased in Cldn7 KO small intestines, whereas it was increased in the large intestines, suggesting the different mechanism that Cldn7 regulates the self-renewal on mouse large and small intestines. Overall, our current study highlights a novel function of Cldn7 in regulating intestinal epithelial stem cell functions and epithelial self-renewal. This study could open a door to study roles of TJ proteins in stem cell regulations in other tissues and organs.
Keywords: Intestinal Mucosa; Claudins